Loop-Mediated Isothermal Amplification (LAMP): Potential Point-of-Care Testing for Vulvovaginal Candidiasis - Meng Li; Xiangyu Jin; Qingyun Jiang; Hongbo Wei; Anni Deng; Zeyin Mao; Ying Wang; Zhen Zeng; Yifan Wu; Shuai Liu; Juhyun Kim; Xiaoqian Wang; et al. (Journal of Fungi, 2023)
Purpose: The aim of this study is to establish a loop-mediated isothermal amplification (LAMP) method for the rapid detection of vulvovaginal candidiasis (VVC). Methods: We developed and validated a loop-mediated isothermal amplification (LAMP) method for detecting the most common Candida species associated with VVC, including C. albicans, N. glabratus, C. tropicalis, and C. parapsilosis. We evaluated the specificity, sensitivity, positive predictive value (PPV), negative predictive value (NPV), and Kappa value of the LAMP method to detect different Candida species, using the conventional culture method and internal transcribed spacer (ITS) sequencing as gold standards and smear Gram staining and real-time Rolymerase Chain Reaction (PCR) as controls. Results: A total of 202 cases were enrolled, of which 88 were VVC-positive and 114 were negative. Among the 88 positive patients, the fungal culture and ITS sequencing results showed that 67 cases (76.14%) were associated with C. albicans, 13 (14.77%) with N. glabratus, 5 (5.68%) with C. tropicalis, and 3 (3.41%) with other species. Regarding the overall detection rate, the LAMP method presented sensitivity, specificity, PPV, NPV, and Kappa values of 90.91%, 100%, 100%, 93.4%, and 0.919, respectively. Moreover, the LAMP had a specificity of 100% for C. albicans, N. glabratus, and C. tropicalis, with a sensitivity of 94.03%, 100%, and 80%, respectively. Moreover, the microscopy evaluation had the highest sensitivity, while the real-time PCR was less specific for C. albicans than LAMP. In addition, CHROMagar Candida was inferior to LAMP in detecting non-albicans Candida (NAC) species. Conclusions: Based on the cost-effective, rapid, and inexpensive characteristics of LAMP, coupled with the high sensitivity and specificity of our VVC-associated Candida detection method, we provided a possibility for the point-of-care testing (POCT) of VVC, especially in developing countries and some laboratories with limited resources.